The effectiveness of bacillus calmette-guerin (BCG) vaccination against leprosy a case-control study in Iloilo Province, the Philippines - Gonzaga, Edgardo M. (2001)
Various prospective studies regarding the effect of Bacillus Calmette-Guerin (BCG) vaccination against leprosy revealed varying results, with levels of protection ranging from 20to 80. A case - control study was conducted at Western Visayas Sanitarium in Sta. Barbara, Iloilo to determine the effect of BCG vaccination against the two subtypes of leprosy, i.e., paucibacillary (PB) and multibacillary (MB). One hundred seventy two cases (86 PB and 86 MB) were chosen from the files of leprosy cases diagnosed from the period January 1997 to June 2000. For each case, one control was selected. Controls were chosen from among the patients who sought medical assistance at the Out Patient Department for dermatological conditions not related to the exposure such as seborrheic, atopic, contact irritant dermatitis and chronic eczematoid dermatitis. The study revealed that BCG vaccination offered protection against multibacillary (MB) leprosy but not consistently with paucibacillary leprosy (PB). For PB type of leprosy, the protective effect of BCG vaccination was noted among single individuals but seems to be a risk factor for married individuals. The protective effect of BCG vaccine on PB type is also greater among low income groups as compared to high income groups. While for MB type, degree of BCG vaccine protection against was higher among single individuals and with no index case in the family. This study provides enough evidence to consider the possible role of BCG vaccination in preventing the development of a more severe type of leprosy among household contacts of MB leprosy.